Thrombocytopenia in malaria. - Looareesuwan, S; Davis, J; Allen, D; Lee, S; Bunnag, D; White, N (1992)
The relationship between platelet counts and platelet bound (direct) or platelet directed (indirect) serum antibody concentrations was studied in 17 patients with Plasmodium falciparum malaria and 12 patients with P. vivax malaria. Platelet counts rose with recovery from infection from 196 +/- 84 x 10(9)/l (mean +/- SD) and 195 +/- 34 x 10(9)/l to 319 +/- 99 and 283 +/- 62 x 10(9)/l respectively (p less than 0.002), but there was no relationship between either absolute platelet count or changes in counts and either indirect or direct platelet antibody levels. These findings suggest that a non-immunologically mediated mechanism is involved in the pathogenesis of thrombocytopenia in malaria.